Investigation into a membrane-assisted crystallizer (MAC) process for Cu2+ removal and recovery from wastewater. (10th April 2020) - Dong, Lihua; Liu, Jing; Wu, Yunyu; Gu, Ping; Hou, Li'an; Chen, Guanyi; Zhang, Guanghui
Abstract: Aiming to prevent the waste of copper resources and improve the reuse rate of wastewater, a membrane-assisted crystallizer (MAC) process was developed to remove and recover Cu 2+ from wastewater. Cu 2+ was sequentially recovered in the form of Cu2 (OH)2 CO3 crystals in a crystallizer and a membrane reactor, where the latter was also used for further solid-liquid separation. To facilitate this recovery, Na2 CO3 and Cu2 (OH)2 CO3 were selected as the precipitant and crystal seed, respectively. Based on the optimized operating conditions, lab-scale MAC processes were evaluated using an initial Cu 2+ concentration of 18.9–52.2 mg/L (tests A, B and C), in which the wastewater was prepared with local tap water that had high concentrations of Ca 2+ (22.6–39.3 mg/L) and Mg 2+ (8.3–9.1 mg/L). The results indicated that the saturation index (SI) and the excess CO3 2− were the decisive factors for normal operation of the MAC process. A well-run MAC process (test A with an SI of 2.67 and an excess CO3 2− of 40 mg/L) not only achieved a lower effluent Cu 2+ concentration (<0.8 mg/L), turbidity (0.1NTU) and a neutral pH (7.6), but also only a small amount of crystal rather than sludge. In addition, owing to the well-growing crystal in the crystallizer, membrane fouling was effectively mitigated and its specific flux could be easily restored via tap water cleaning (≥90%). More importantly, SEM and EDS analyses indicated that Cu 2+ was selectively recovered in the form of Cu2 (OH)2 CO3 crystals with traces of Ca and Mg. Therefore, they can be directly recovered or continue to be used as the seed crystal. That is, Cu2 (OH)2 CO3 (0.1 wt%) only needs to be added in the first cycle. Therefore, the MAC process is an environmentally friendly technology. Graphical abstract: Image 1 Highlights: A membrane-assisted crystallizer process was developed to remove and recover Cu 2+ . Cu 2+ was selectively removed from 18.9 to 46.8 mg Cu 2+ /L to <1.0 mg Cu 2+ /L or less. Cu 2+ was recovered in the form of Cu2 (OH)2 CO3 crystal with traces of Ca and Mg. Less chemical used, the seed only needs to be added in the first cycle (0.1 wt %). Membrane-specific flux can be restored to more than 90% via tap water cleaning.